KEDUDUKAN DAN KEWENANGAN PEMERINTAH KECAMATAN MENURUT UDANG-UNDANG NOMOR 32 TAHUN 2004 TENTANG PEMERINTAHAN DAERAH - Fajar Nugraha Pandji, Anak Agung Ngurah; Parsa, I Wayan; Sarna, Kadek (Kertha Negara : Journal Ilmu Hukum; Vol. 01, No. 06, September 2013)
Large and the number of government affairs, it is not possible entirely administered by the central government, located in one place. To help the government affairs, state governments need assistance in the region to achieve the purpose of the State as defined in the preamble to the Constitution of the Republic of Indonesia 1945. Based on this background, the formulation of the problem is, Is there any delegation of authority from the Regent / Mayor or District / town. Using writing to the Government District normative. Tool District / City led by Chief District called. Chief District in carrying out his duties as the area receives delegation of authority from the Regent / Mayor. Chief District also always guided and refer to the same regulations as for example the Law, Government Regulation, Government Regulation and Regulation as seen from Autonomy system current.
Keywords: position, authority, district government